PENGARUH LINGKUNGAN ETIKA, PENGALAMAN AUDITOR DAN TEKANAN KETAATAN TERHADAP KUALITAS AUDIT JUDGMENT - Pritta Amina Putri; Herry Laksito (Diponegoro Journal of Accounting, 2013)
This research was aimed to obtain empirical evident whether there is any effect of environtmental ethics, auditor’s experience and obedience pressure toward audit judgment taken by auditor. This research was carried out at the Central Java especially in Semarang city with respondent  from auditors who work in Public Accountant Office in Semarang city.            The sampling was conducted by purposive judgment sampling technique. The criterias are auditor who worked on the Public Accountant Office  (KAP), especially in Central Java, Semarang city,  listed on Compartment IAI Directory Public Accountant in 2012, and has worked at least 1 year experience. Data is collected using questionnaires distributed as 75 and only 43 questionnaires that can be processed. Data analysis using multiple linear regression.            The results of this study showed that ethical environment, auditor’s experience and obedience pressure,  has a positive influence on quality of audit judgment.